The socratic method online to improve critical and high order thinking among students - Md. Suhadi, Salihuddin (2014)
Since the existance of social sites is more widespread nowadays; adolescents ages 13 to 17 are often engaged in it more than studying. These things happen because they are exposed to the use of technology since birth. This can be avoided since technology can be put to good use in daily or everyday life. Various parties, especially parents and teacher should monitor their children’s addiction to technology can be deflected to thing that can be beneficial. For example, the use of online learning is an ideal medium for students who often use the computer while studying. The use of online technology for learning can help student to share ideas with other students and socialize at the same time (Liao et al., 2014). Apart from that, there are also studies that state the online learning can stimulate the student’s use of critical thinking as they challenged each other to express their views (Kalelioglu dan Gülbahar, 2014). To futher improve the online discussion, the use of socratic method which is a method that can make students always think. This due to the fact that this method uses questioning techniques to encourage students to think for acquiry answers, thus construct their own concept of the answers given and received from their peers in the forum (Yang et al., 2005).